GATA1-mediated macrophage polarization via TrkB/cGMP–PKG signaling pathway to promote the development of preeclampsia - Wushan Li; Fei Hou; Di Cheng; Fengchun Gao; Jin Wang; Baoxia Cui (European Journal of Medical Research)
Abstract Background Preeclampsia (PE) is a severe pregnancy complication characterized by hypertension and proteinuria. PE poses a substantial threat to the health of both mothers and fetuses, and currently, there is no definitive treatment available. Recent studies have indicated that the transcription factor GATA1 may be implicated in the pathological processes of PE, but the underlying mechanism remains elusive. NTRK2/cGMP–PKG signaling pathway plays a crucial role in regulating the function and polarization of macrophages, which are key immune cells at the maternal–fetal interface. This study aims to investigate the role of GATA1 in the pathogenesis of PE, with a specific focus on how GATA1-regulated TrkB/cGMP–PKG signaling in macrophages and its dysregulation contribute to the development of preeclampsia. Methods By employing THP-1 cells, co-culture systems of THP-1 cells and HTR-8/Svneo, HPVECs and Sprague–Dawley (SD) rats, in conjunction with gene knockdown and overexpression techniques, we explored the effects of GATA1 on the TrkB/cGMP–PKG signaling pathway. Transcriptomic sequencing, bioinformatics analysis, animal experiments, and clinical sample collection were conducted to validate the role of GATA1 in PE. Results Knockdown of GATA1 mitigated the symptoms of PE, and this effect was reversed by overexpression of TrkB. In comparison with the control group, the proportion of M2 cells elevated significantly in the sh-GATA1 group (P < 0.001). In addition, the protein expressions levels of TrkB, cGMP, and PKG were significantly decreased in the sh-GATA1 group were significantly decreased compared with those in the control group (P < 0.001, P < 0.001, P < 0.001, P < 0.05, respectively). Moreover, knockdown of GATA1 significantly promoted the migration rate and blood vessel formation of HTR-8/Svneo cells (P < 0.001, P < 0.05, respectively) which inhibited by overexpression of NTRK2 (P < 0.05, P < 0.01, respectively). Conclusions The study demonstrated that knockdown of GATA1 modulates M2 polarization of macrophage through the TrkB/cGMP–PKG signaling pathway, influencing the progression of PE. In addition, significant associations between GATA1 and the TrkB/cGMP–PKG signaling pathway were identified in the transcriptomic data from PE patient placentas.